Landscape pattern simulation in Xinyang City and its driving factors analysis from 2001 to 2025 - Huo, Zehua (The University of Edinburgh, 2021)
As the demand for living space and development increases due to population growth worldwide, the depletion of natural resources such as forests dramatically increases, which has led to a number of environmental problems. The protection of forest resources has gradually become the consensus of mankind, governments all over the world have introduced policies on forest protection. Regular monitoring of urban land use statistics and analysis of the trends in land use can help local governments better implement relevant policies, rationalize the allocation of natural resources and reduce the risks caused by environmental problems. By simulating land use change and its trends in Xinyang City from 2001 to 2025 with Landsat series satellite imagery, the paper identifies changes in different land use landscape patterns, and analyses and interprets its driving factors using socio-economic statistics. The conclusions of this paper are: (1) the dominant land use types of Xinyang City are farmland and forest; (2) more than half of the forests in Xinyang City have been transformed into crop land or built-up area while changes in water area and unused land are insignificant; (3) the overall landscape patten abundance of Xinyang City has increased, but the fragmentation of forests has increased significantly with the dominance decreased by 85%, and the forest spatial pattern will be further compressed in 2025, if the current land use trends continue; (4) changes in forest area, as the cost of development, and socio-economic factors have showed significantly negatively correlated, and the urban heat island effect has slightly increased.
Keywords: Landscape pattern simulation; Landsat series satellite imagery; CA-Markov model; land use classification; Xinyang City